RELATIONSHIP BETWEEN PSYCHOLOGICAL CAPITAL AND WITHDRAWAL BEHAVIOR: THE MEDIATING ROLE OF PSYCHOLOGICAL OWNERSHIP (Third Sector Social Economic Review, 2020)
TThe aim of this study is to investigate the effect of psychological capital on the withdrawal behavior and to investigate whether psychological ownership has a mediating effect in this relationship. In the study, data was collected from 557 employees of a private sector in Konya using simple random sampling method and survey technique. The data collected in the study were analyzed through SPSS 23 package program. Analysis for the research hypotheses was tested through Process Macro. As a result of the research, it has been determined that psychological capital has a positive and significant effect on psychological ownership. In addition, the study concluded that psychological capital has a negative and significant effect on the withdrawal behavior. Within the scope of the study, it was determined that psychological ownership has a mediating role in the effect of psychological capital on the withdrawal behavior.
Keywords: Psychological Capital; Psychological Ownership; Withdrawal Behavior; Mediator Effect.